State space predictive controller and estimator of inverted pendulum - Chen, Yini. (2008)
State space generalized predictive controller has been successfully designed by K.V.Ling and K.W. Lim ( 1996 ). It is tested in controlling an inverted pendulum system with satisfactory results ( Yong Tet Leong, 1998 ). But this controller is designed and applied based on the assumption that all states can be measured for constructing the state feedback. This is not a practical assumption in real applications. To deal with processes with inmeasurable variables, an estimator state space GPC is designed.